BUDAYA ETIS ORGANISASI, KEEFEKTIFAN SISTEM PENGENDALIAN INTERNAL, DAN PENEGAKAN HUKUM TERHADAP TERJADINYA FRAUD DI SEKTOR PEMERINTAHAN (Persepsi Pegawai Organisasi Perangkat Daerah Kota Tangerang) - Dian Maruli Tua Pohan (POLITEKNIK LP3I JAKARTA, 2021)
This study aims to analyze and examine the influence of organizational ethical culture, internal control and law enforcement on the occurrence of fraud. The population in this study were all employees of the Regional Apparatus Organization (RAO) in Tangerang City, totaling 24 RAOs. The sample in this study using convenience sampling technique as many as 110 respondents. The data collection technique uses a questionnaire survey: The type of data used in this study is original data that was collected by sending a questionnaire survey to respondents. This research is a type of quantitative research, which is research that focuses on using statistical analysis tools to test hypotheses and draw general conclusions. The data analysis technique used the Structural Equation Model (SEM). Data sources are the opinions and perceptions of every personnel in the Regional Apparatus Organization (RAO who are responsible for making or compiling financial reports. The results of this study indicate that: 1) The ethical culture of the organization has a significant negative effect on the occurrence of fraud. 2) The effectiveness of the internal control system has a significant negative effect on the occurrence of fraud. 3) Law enforcement has a significant negative effect on the occurrence of fraud.Keywords: Organizational Ethical Culture, Internal Control Systems, Law Enforcement, Fraud